The political department and the retraction of paramountcy in India 1935-1947 - Moëd, Madeleine (Rhodes University, Faculty of Humanities, Department of History, 1988)
The Political Department and the Indian Political Service stand accused of sins of omission and commission. The evidence suggests that they were badly hampered by ill-conceived training prodecures, a lack of manpower and above all the incoherent policy of the British government towards the Indian states. The failure of the 1935 Federation Act which formally established the Political Department was not due to princely intransigence inspired by political officers. Between 1935 and 1947 the Political Department embarked on a vigorous programme of combining the resources of the smaller states to strengthen them as viable partners in a new India. Their lack of success in effecting the federation of the states with India in 1947 was not a result of the disinclination of political officers to implement reform as much as their inability to do so. Many princes were also unwilling to sacrifice a measure of sovereignty for efficient government and paramountcy precluded forcing internal reform on the princes. Paramountcy was never clearly defined and thus its retraction in 1947 took place amidst confusion and misunderstanding on all sides. The Indian Political Service was always treated as secondary to the Indian Civil Service and the states to British India. Britain's emphasis on constitutional change in British India, reflected in the Cripps Mission of 1942, the Cabinet Mission of 1946 and the rush towards independence in 1947 resulted in her inattention to the Political Department and the princes which culminated in the abandonment of both in 1947.
Keywords: India; India -- Politics and government -- 1919-1947